Deskripsi Penerapan Permainan Susun Warna Ceria untuk Menstimulasi Motorik Halus Anak Usia Dini - Sri Deyanti Paluwala; Fitriani Maun; Nabila Rahdani Mandjurungi; Pupung Puspa Ardini; Nadia Luawo; Salma Rahman; Siti Maryam Pomalo (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Fine motor skills are an essential aspect of early childhood development, as they involve the ability to use small muscles, particularly those of the fingers and wrists. These skills are required for various activities, such as grasping, transferring objects, arranging items, drawing, and writing. This study aims to describe the